Mercury Induced Immunological Disorders - Abdurrosyid, Muhammad; Ekawanti, Ardiana; Ayunda, Rahmah Dara (PROMOTOR, 2025)
The immune response to mercury is unique, it can be immunosuppressive and immunomodulative. The immune response to mercury begins with exposure to mercury from the environment originating from natural activities such as volcanic activity and human activities such as gold processing from artisanal small scale gold mining and chlorine alkali factories, or from consumption mercury- contaminated fish. These mercury sources release inorganic and organic mercury which enters the human body through inhalation, ingestion and absorption through the skin. The entry of mercury into the body will induce innate and adaptive immune responses. The immune response to mercury is immunomodulative and triggers proinflammatory substances production. This mechanism is the pathological basis for clinical manifestations of mercury intoxication in the kidneys, central nervous system, respiratory tract and skin.